(untitled) (Informatica, 2021)
Context-aware computing refers to system ability to sense its environment and modify its behavior for delivering suitable services. Having such kind of systems with the Near Field Communication (NFC) capability, opens new perspectives and research areas, allowing very useful type of applications known as NFC-based context-aware applications. These systems require correctness due to their applicability and then need to be proven formally using exhaustive analysis approach such as formal verification. In literature, most of works focuses on creating a general model for context aware systems ignoring the specificity of certain applications such as NFC applications where they present a higher complexity. We emphasize the existence of little or no work in this area supporting formal modeling. To boost it, we propose BigNFC as a novel formal-model based on Bigraphical Reactive Systems (BRS) taking account the interaction mode from the beginning, so we establish mapping between BRS and BigNFC components, where the structures are modelled as bigraphs and behaviors as rewriting rules. Finally, to validate our model, we have applied it on a real-life application and some properties were checked successfully.